2009
DOI: 10.1155/2009/817837
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Nitroglycerin as an Adjuvant to Patient‐Controlled Morphine Analgesia after Total Knee Arthroplasty

Abstract: The use of NTG patches conferred no advantage over the use of placebo in patients receiving patient-controlled morphine analgesia after total knee replacement. Two myocardial infarcts occurred in this group. Therefore, the safety of postoperative NTG patch use for pain control must be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…In the study of Orbach-Zinger et al, nitroglycerin patches showed no advantage in patients receiving PCA of morphine analgesia after total knee replacement. Therefore, they realized that the safety of using nitroglycerin patch after the surgery must be investigated more (11), this finding was inconsistent with our study and it seems the cause of this difference is the dosage of nitroglycerin in these two studies and underlying disease of studied patients as well.…”
Section: Discussioncontrasting
confidence: 89%
“…In the study of Orbach-Zinger et al, nitroglycerin patches showed no advantage in patients receiving PCA of morphine analgesia after total knee replacement. Therefore, they realized that the safety of using nitroglycerin patch after the surgery must be investigated more (11), this finding was inconsistent with our study and it seems the cause of this difference is the dosage of nitroglycerin in these two studies and underlying disease of studied patients as well.…”
Section: Discussioncontrasting
confidence: 89%
“…Some studies investigated the effectiveness of nitroglycerin in relieving the pain of patients who had arthroscopic knee surgery (6), chronic pain after thoracotomy (7), and diabetic neuropathy (8). Researchers also reported that the systemic use of nitroglycerin was useful in patients who had spinal anesthesia (9).…”
Section: Introductionmentioning
confidence: 99%